2022
DOI: 10.1038/s41598-022-15527-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated electrocoagulation-flotation of microalgae to produce Mg-laden microalgal biochar for seeding struvite crystallization

Abstract: Developing sustainable materials for recovering and recycling nutrients from wastewater is critically needed for nutrients such as phosphorus that have a diminishing supply. Struvite crystallization is emerging as a promising strategy for phosphorus recovery which can be enhanced with seeding through microalgal biochar. The main bottleneck of using microalgae is its high harvesting cost. In this study, an integrated electrocoagulation-flotation (ECF) process is used to recover and at the same time modify the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…With the biochar modification (i.e., Fe‐BC P in this study), the Fe treatment on the biochar creates nanoparticulate iron oxide (e.g., hydrous ferric oxide) that increases the adsorption affinity of the biochar for P (Bakshi et al, 2021; Zhang et al, 2020). This is supported by studies that show metal modifications on biochar facilitate the formation of metal‐biochar bridges between phosphate anions and negatively charged weak‐acid functional groups on the biochar (Garcia‐Perez et al, 2022; Kubar et al, 2021; Nageshwari et al, 2022).…”
Section: Resultsmentioning
confidence: 85%
“…With the biochar modification (i.e., Fe‐BC P in this study), the Fe treatment on the biochar creates nanoparticulate iron oxide (e.g., hydrous ferric oxide) that increases the adsorption affinity of the biochar for P (Bakshi et al, 2021; Zhang et al, 2020). This is supported by studies that show metal modifications on biochar facilitate the formation of metal‐biochar bridges between phosphate anions and negatively charged weak‐acid functional groups on the biochar (Garcia‐Perez et al, 2022; Kubar et al, 2021; Nageshwari et al, 2022).…”
Section: Resultsmentioning
confidence: 85%
“…Biochar sorbents are less expensive than struvite or direct sludge water applications and the phosphorus from the biochar is more bioavailable to plants. From these studies, we can see the promise of biochar for recycling waste feedstocks into useful adsorbent carriers of nutrients, as alternative crystallizing agents for struvite that could replace more expensive chemical precipitants, or as sorbents for the removal of pollutants from wastewaters …”
Section: Using Wastes and Wastewater As Nutrient Sourcesmentioning
confidence: 99%
“…It was found that the applied current, the CaCO 3 particle size, and the feed rate can affect calcium phosphate precipitation . As an alternative seeding agent microalgae-derived biochar enriched with magnesium has also been used for seeding struvite crystallization …”
Section: Chemical Processesmentioning
confidence: 99%
“…From these studies and more we can see the promise of biochar for recycling waste feedstocks into useful adsorbent carriers of nutrients or other products, as alternative crystallizing agents for struvite potentially replacing more expensive chemical precipitants, or as sorbents for the removal of pollutants from wastewaters. 114 In the following study on the hydrothermal carbonization of digestate, an anaerobic digestate may be used to recover nutrients. Hydrothermal carbonization of anaerobically digested biomass is a way to make another biochar, referred to by the authors as "hydrochar" due to the process used to make it.…”
Section: Using Wastes and Wastewater As Nutrient Sourcesmentioning
confidence: 99%
“…156 Microalgae-derived biochar enriched with magnesium has been used for seeding struvite crystallization. 114 In Ion-Exchange Membrane Electrodialysis (ED), extraction of nutrients from wastewater occurs via application of ion-exchange membranes. 157 Over 95-98% of the phosphate and nitrate nutrients were recovered from the wastewater from a membrane bioreactor using ion exchange.…”
Section: Chemical Processesmentioning
confidence: 99%